2023
DOI: 10.1007/s40291-023-00672-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Potential Antioxidant Therapies in Vitiligo: A Narrative Review

Aleksandra Białczyk,
Adam Wełniak,
Barbara Kamińska
et al.

Abstract: Vitiligo is a chronic skin disorder characterised by the loss of melanocytes and subsequent skin depigmentation. Although many theories have been proposed in the literature, none alone explains the pathogenesis of vitiligo. Oxidative stress has been identified as a potential factor in the pathogenesis of vitiligo. A growing body of evidence suggests that antioxidant therapies may offer a promising approach to managing this condition. This review summarises the potential mechanisms of oxidative stress and the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 135 publications
0
4
0
1
Order By: Relevance
“…The skin is the largest organ in contact with the environment, and UV exposure makes melanocytes more likely to generate excess ROS when synthesizing melanin [ 1 , 4 , 5 , 29 , 30 ]. Previous studies have found that the entire epidermis of patients with vitiligo could be in a state of oxidative stress due to the accumulation of a large quantity of H 2 O 2 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The skin is the largest organ in contact with the environment, and UV exposure makes melanocytes more likely to generate excess ROS when synthesizing melanin [ 1 , 4 , 5 , 29 , 30 ]. Previous studies have found that the entire epidermis of patients with vitiligo could be in a state of oxidative stress due to the accumulation of a large quantity of H 2 O 2 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, antioxidants might play a potential role in managing vitiligo, addressing oxidative stress, especially in conjunction with phototherapy; however, results from psoriasis studies also suggest that NBUVB might exert intrinsic antioxidant effects on its own 114,115 . In one study, the addition of alpha‐lipoic acid did not provide further benefit to NB‐UVB therapy in the treatment of stable NSV, whereas in another, pre‐treatment and concurrent supplementation with alpha‐lipoic acid before and during NB‐UVB significantly enhanced the clinical effectiveness of NBUVB and reduced vitiligo‐associated oxidative stress 116,117 .…”
Section: Clinical Aspects Of Phototherapy Treatment In Vitiligomentioning
confidence: 99%
“…Nghiên cứu về giả thuyết tự miễn cho thấy vai trò của miễn dịch tế bào và cytokin viêm trong sự phát triển của bệnh bạch biến [5][6][7] . Giả thuyết stress oxy hóa cũng được ủng hộ bởi nghiên cứu ghi nhận nồng độ gốc oxy hóa cao bất thường trong mô thượng bì tổn thương bạch biến, dẫn đến suy chức năng và chết tế bào sắc tố 8,9 . Nguyên nhân của các tình trạng này đến nay chưa được biết rõ, và người ta đề xuất rằng kẽm -một chất vừa có vai trò điều hòa miễn dịch vừa có khả năng chống oxy hóa -bị thiếu hụt ở bệnh nhân bạch biến không phân đoạn.…”
Section: đặT Vấn đềunclassified